A cross-sectional study examining the relationship between nursing practice environment and nurses’ psychological empowerment - Kikuko Taketomi; Yasuko Ogata; Miki Sasaki; Yuki Yonekura; Michiko Tanaka (Scientific Reports)
Abstract The nursing practice environment is essential for improving the quality of nursing practice and patient service. Performing secondary analysis of data from the work environment for hospital nurses in Japan (WENS-J) study, this research investigated whether an improved, healthier work environment could enhance nurses’ psychological empowerment. Self-administered questionnaire responses of 2,438 participants from 23 participating general hospitals with over 200 beds in municipalities with a population of 200,000 or more were analyzed. The questionnaire recorded participating nurses’ demographic characteristics and utilized two scales: the Practice Environment Scale of the Nursing Work Index (PES-NWI) and the Psychological Empowerment Instrument (PEI), which identified adequate work environments and measured the internalization of organizational goals and objectives, respectively. Most participants (93.7%) were female nurses with a mean age of 33.7 years. Multilevel analysis (hierarchical linear models) revealed that the total PEI score was significantly related to the PES-NWI composite score and all subscales after adjusting for nurses’ demographic characteristics, such as age (coefficient 0.33–0.72, all p < .001). The results suggest that a work environment such as that presented in the PES-NWI may contribute to nurses’ psychological empowerment. These findings could provide insight for creating healthier work environments.